Enhancing Government Capacity for Air Quality Management in the Philippines through Geospatial Technologies: A Case of Project AiRMoVE - R. Ramos; R. Ramos; A. Tamondong; A. Tamondong; R. A. Torres; B. A. Recto; K. Panlilio; R. R. Sta. Ana; M. L. Tinio; T. Yumul-Calzado; B. Carcellar III; B. Carcellar III; et al. (ISPRS Annals of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
Air quality management is crucial in the Philippines due to its profound implications for public health, ecosystems, and sustainable development. Project AiRMoVE, short for the Ambient Air Remote Sensing, Modeling, and Visualization Environment project, aims to enhance air quality management through engineering solutions and geospatial technologies such as remote sensing (RS), geographic information systems (GIS) and numerical modeling. Implemented by the University of the Philippines Training Center for Applied Geodesy and Photogrammetry (UP TCAGP), Project AiRMoVE collaborates with key stakeholders to identify attainment and non-attainment areas in the National Capital Region (NCR) for air quality monitoring. This paper provides an overview of Project AiRMoVE's objectives, methodologies, and outcomes, emphasizing the significance of RS and GIS in revolutionizing air quality monitoring and management. It underscores a systematic approach adopted in enhancing government capacity for air quality management -- a combination of workshops, technical trainings, and stakeholders' forums.